Metode Al-‘Urf Dalam Menyimpulkan Hukum Islam - Muhammad Yusril; Dhiauddin Tanjung (Peduli Riset dan Pengabdian Masyarakat, 2024)
This research discusses al-'urf which is one of the bases for making laws in the Islamic religion. Al-'urfini takes the law from something that is familiar to society, which has become a habit and is integrated into their lives, whether in the form of actions or words. Of course, without violating the basic teachings of Islam contained in the Koran and al-Sunnah. The method used is qualitative research with a liberal research approach. Researchers conducted literature searches through various sources such as scientific journals, books, articles and other related publications. The results of the research show that the al-'urf method of Islamic law can be familiar, grounded and accepted in the midst of a pluralistic society, without having to abandon its basic principles. An examination of this concept is also an answer for contemporary Muslim thinkers who often push for reform of Islamic law through the mechanism of deconstructing Islamic law and adapting it to the principles of human rights.